Ca0.89Tm0.007Ho0.003Yb0.1MoO4 phosphor for nonthermally coupled level-based temperature sensing and latent fingerprint detection - Singh S.; Vishwakarma P.K.; Sharma M.; Singh S.K. (My University, 2025)
This study explores the spectral feature of Ln3+ (Ho3+, Tm3+, Yb3+) doped CaMoO4 phosphor for non-thermally coupled levels (NTCLs) based temperature sensing and latent fingerprints (LFPs) detection. Phase analysis of hydrothermally synthesized CaMoO4:Ln3+ phosphors, reveals the formation of tetragonal lattice with I41/a space group. An increment in particle size has been observed due to modification caused by doping of Ho3+/Tm3+/Yb3+ ions. Fourier transform infrared spectroscopy (FTIR) study corroborates the desired lattice formation, while UV–Vis analysis indicates a significant reduction in optical bandgap after incorporating Ln3+in the CaMoO4. Optical properties of Ho3+ and Tm3+ ions, individually or in combination with Yb3+ ions, demonstrate strong Upconversion (UC) emission spanning the visible region. Temperature-dependent emission of Ho3+/Tm3+ is employed for temperature sensing based on NTCLs fitted by Boltzmann sigmoidal function, which reveals the maximum temperature sensitivity for the I795/I473 (69.86×10−2 K−1 at 500 K). In addition, the luminescent phosphor materials have also been demonstrated for LFP detection through the powder dusting technique. Conclusively, these phosphor materials show multifunctionality and great potential for optical applications. © 2025 Elsevier B.V.